Investigations into the effects of material filters (Cu 0.125mm and Al 0.2mm) on image linearity in Tc-99m SPECT - Shah, Syed Inayatullah; Yee, Fong Shu (Research Publish Journals, 2016)
Performance parameters, e.g., spatial linearity and uniformity of single photon emission computed tomography (SPECT) imaging systems are affected by scattered gamma events. Hence, the quality of the reconstructed image is degraded. In this study, material filter method was employed for reducing the adverse effects of scatter events from the Tc-99m spatial linearity images. Material filters work by absorbing the scattered gamma photons before they can reach the surface of the detector of the gamma camera. The filters used were copper (Cu) 0.125mm and aluminum (Al) 0.2mm thick flat sheets. SPECT data were collected by scanning Carlson’s phantom with the linearity insert. The radionuclide, Tc-99m was injected into the phantom. Symmetrical energy window (+/-10% centered at 140keV) was selected. Filters were separately mounted on the outer surface of the gamma camera (GCA-901A/HG) with either low energy general purpose or low energy high resolution collimator. Results of material filtered data images show improvement in the image linearity. It is concluded that material filters have the potential to improve overall image quality in Tc-99m SPECT.